A psychometric evaluation of the University of Auckland General Practice Report of Educational Environment: UAGREE. Issue 2 (4th March 2017) - Eggleton, Kyle; Goodyear-Smith, Felicity; Henning, Marcus; Jones, Rhys; Shulruf, Boaz
Abstract: Purpose : The aim of this study was to develop an instrument (University of Auckland General Practice Report of Educational Environment: UAGREE) with robust psychometric properties that measured the educational environment of undergraduate primary care. The questions were designed to incorporate measurements of the teaching of cultural competence.Methods : Following a structured consensus process and an initial pilot, a list of 55 questions was developed. All Year 5 and 6 students completing a primary care attachment at Auckland University were invited to complete the questionnaire. The results were analysed using exploratory factor analysis and confirmatory factor analysis resulting in a 16-item instrument.Results : Three factors were identified explaining 53% of the variance. The items' reliability within the factors were high (Learning: 0.894; Teaching: 0.871; Cultural competence: 0.857). Multiple groups analysis by gender; and separately across ethnic groups did not find significant differences between groups.Conclusion : UAGREE is a specific instrument measuring the undergraduate primary care educational environment. Its questions fit within established theoretical educational environment frameworks and the incorporation of cultural competence questions reflects the importance of teaching cultural competence within medicine. The psychometric properties of UAGREE suggest that it is a reliable and valid measure of the primary care education environment.